ACTIVITY OF MARTICARIA CHAMOMILLA CRUDE AND TOTAL FLAVONOID EXTRACTS AS ANTI-VIRULENCE FACTOR FOR CLINICALLY ISOLATED PSEUDOMONAS AERUGINOSA - Sarah N. L.,; Zainab F. M., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to examine and detect the total flavonoid presence from the crude extract use in phytochemical test and HPLC device, and detecting  on both extract by UV-spectrophotometer. The objective of this study for inhibition the pyocyanin pigment that produce by pseudomonas aeruginosa by use Marticaria chamomilla crude and flavonoid extract.  The extraction of chamomile was accomplished by methanol 80%, where different concentrations and dilutions of the crude and flavonoid extract and used as anti-virulence factor. 130 clinical samples of burns and wounds where collected from patients in the medical city hospital. The result showed that 44 isolates where identified as  P.aeruginosa using the vitik 2 test, and 19 isolates that can ability to produce pyocyanin pigment, when they were sub-culturing on king A medium. Isolate No. 33 was selected are the largest produce of pyocyanin and most resistance bacteria to antibiotics, as the anti-bacterial sensitivity test was compacted using five type antibiotics (Levofloxacin, Polymyxin, Piperacillin, Imipenem, Tetracycline).  the result also slowed that the flavonoid extract inhibited pyocyanin pigment better than the crude extract and the concentration of 950 mg/ml in the first dilution where the flavonoid give 28mm in diameter of inhibition zone when compare with crude extract that give 25mm in diameter inhibition zone for pyocyanin.